2021
DOI: 10.1021/acsaem.1c02733
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Indoline-Based Unsymmetrical Squaraine Dyes for Dye-Sensitized Solar Cells: Modulating the Dye-TiO2/Electrolyte Interface for Nonaqueous and Aqueous Electrolytes

Abstract: A high molar extinction coefficient with sharp absorption properties from the range of visible to near-infrared regions makes squaraine dyes very attractive and potential chromophores for dye-sensitized solar cell (DSSC) applications. Here, we report a series of alkyl groups and glycolic chain [triethylene glycol (TEG)]-wrapped amphiphilic indoline-based unsymmetrical squaraine dyes, where the number of carbon atoms in the alkyl groups and TEG was systematically changed by incorporating the alkyl groups and TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…Here, the SQ5 and SQS4 dyes formed well-packed controlled aggregated structures in the bad sensitizing solvent and showed better IPCE responses (more than 50%) compared to the SQ1 dye without CDCA; further addition of CDCA enhanced IPCE responses for all of the three dyes. Aggregated structures of D-A-D based squaraine dyes are the results of facile Ti periodic sites in TiO 2 (101 facet), which facilitate the formation of aggregates. ,, Such types of monomeric, dimeric, aggregated, and highly aggregated structures have been also observed for D-A-D based squaraine dyes at the air–water interface, in aqueous solutions, in DMSO–water mixtures, in microheterogeneous media, and in Langmuir–Blodgett films. Further, the lengths of the hydrophobic alkyl group in the squaraine dye showed relatively high V OC and J SC values in the bad sensitization solvent compared to that in the good solvent. Such high photovoltaic parameter values were observed due to the better surface passivation and controlled dye aggregation, whereas the low V OC and J SC values in the good sensitizing solvent are due to low dye loading for all of the dyes (Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…Here, the SQ5 and SQS4 dyes formed well-packed controlled aggregated structures in the bad sensitizing solvent and showed better IPCE responses (more than 50%) compared to the SQ1 dye without CDCA; further addition of CDCA enhanced IPCE responses for all of the three dyes. Aggregated structures of D-A-D based squaraine dyes are the results of facile Ti periodic sites in TiO 2 (101 facet), which facilitate the formation of aggregates. ,, Such types of monomeric, dimeric, aggregated, and highly aggregated structures have been also observed for D-A-D based squaraine dyes at the air–water interface, in aqueous solutions, in DMSO–water mixtures, in microheterogeneous media, and in Langmuir–Blodgett films. Further, the lengths of the hydrophobic alkyl group in the squaraine dye showed relatively high V OC and J SC values in the bad sensitization solvent compared to that in the good solvent. Such high photovoltaic parameter values were observed due to the better surface passivation and controlled dye aggregation, whereas the low V OC and J SC values in the good sensitizing solvent are due to low dye loading for all of the dyes (Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…The device performance of SQ dyes were measured under standard simulator condition (AM 1.5 G, 100 mW cm −2 ), where the area of the black mask was 0.36 cm 2 . The solvents used for sensitization and electrolyte solutions were deoxygenated by purging with nitrogen gas (22).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, modulation of various device components such as anode, cathode, electrolyte and light‐absorbing sensitizers make the dye‐sensitized solar cell (DSSC) (2–7) very attractive, besides other third‐generation photovoltaic technologies. Organic sensitizers offer different architectures to enhance the light‐harvesting properties of the dyes, such as D‐A (8–10), D‐π‐A (11–13), D‐A‐π‐A (14,15), D‐D‐π‐A (16,17), and D‐A‐D (18–23) types. Furthermore, dyes with a broad spectral response is vital besides the NIR‐light absorption and co‐sensitization for the enhanced photocurrent generation (24–29).…”
Section: Introductionmentioning
confidence: 99%
“…In DSSCs, the electrolyte plays a very important role in both dye reduction regeneration and charge transfer. The liquid electrolyte is the most widely used, but its leakage and sealing problems still limit the practical commercial application of DSSCs. , Currently, gel electrolytes can be utilized to replace the liquid electrolytes to overcome these limitations. Specifically, polymer gel electrolytes were reported to have great advantages, including their relatively high ionic conductivity, high permeability in porous titanium dioxide membranes, and thermal stability. Table S1 lists the photovoltaic parameters that have been related to the development of quasi-solid-state electrolyte DSSCs in recent years. , So far, many polymers and copolymers, such as polypyrrole, polyethylene oxide (PEO) polyacrylonitrile, poly­(acrylic acid- co -ethylene glycol), and poly­(acrylic acid), have been successfully used to prepare gel electrolytes. To further improve the efficiency of the cell, many studies have focused on the utilization of various nanomaterials, such as clay, graphene, carbon nanotubes, metal oxides, and so forth. For example, Venkatesan et al reported a graphene oxide (GO) sponge as a printable electrolyte for nanofillers in a mixed polymer for quasi-solid-state DSSCs (QS-DSSCs), to achieve a PCE of 8.78% . In addition, Yu et al introduced three different metal oxide nanoparticles (SiO 2 , TiO 2 , and ZnO) into the electrolyte to improve ion dispersion and charge transportation, in which the DSSC containing 15% TiO 2 nanoparticles achieved the best performance of 8.32%.…”
Section: Introductionmentioning
confidence: 99%